Evaluation of Drought Tolerance Selection Indices in Chickpea Genotypes - Jha, Uday Chand; Basu, Parthasarathi; Shil, Sandip; Singh, Narendra Pratap (International Journal of Bio-resource and Stress Management, 2016)
Drought or soil moisture stressremains one of the most important abiotic stresses; limiting chickpea yield worldwide. In order to identify drought tolerant chickpea genotype, 34 genotypes (13 desi and 21 kabuli including 4 checks) were evaluated under irrigated and moisture stressed condition in randomized complete block design (RBD) with three replications during 2013−14. Six drought tolerance indices viz, mean productivity (MP), geometric mean productivity (GMP), yield index (YI), tolerance index (TOL), stress susceptibility index (SSI), and superiority measures (SM) were implicated on the basis of grain yield in moisture stress (Ys) and well irrigated (Yp) conditions. Genotypes viz. FLIP03-100, FLIP05-123C, FLIP03-98C, IPC2009-102 and IPC2009-186 were found to be superiorgenotypes based on MP and GMP drought tolerant indices under moisture stress condition. High significant positive correlations were recorded between MP and GMP (0.944**), MP and YI (0.984**), TOL and SSI (0.877**) and GMP and YI (0.984**) indices. Principal component analysis lowered the six indices into two components first and second component justifying 97.9% of the variations (84.63 and 13.34% for PC1 and PC2, respectively). Further, the genotypes were grouped into 4 groups by two ways cluster analysis (using Ward’s method) based on Yp, Ys and drought tolerance indices. Importantly, the results of correlation, 3D graphs, bi-plot and cluster analysis reveals that the most suitable indices to screen chickpea genotypes in drought stress conditions were MP, GMP and YI. Therefore, these indices may be useful for selection of drought tolerant chickpea genotypes.